The Silent Crisis in the Education Sector: A Study of the Impact of Budget Cuts in Indonesia and the United Kingdom: (Krisis Diam-Diam di Sektor Pendidikan: Studi Dampak Pemangkasan Anggaran di Indonesia dan Inggris) - Endah Khairunnisa; Nur Habibah; Andini Putri Utami (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
Education budget cuts often occur without sufficient public scrutiny, despite their profound implications for the quality of educational services. This study compares the impact of budget reductions in Indonesia and the United Kingdom—two countries with differing educational systems and development levels. Using a qualitative-comparative approach, this research investigates policy shifts, institutional responses, and their consequences on access, quality, and equity in education. Data were obtained through policy document analysis, international reports, interviews, and media sources. The findings reveal a parallel trend in both countries where budget cuts have exacerbated inequality, reduced support for vulnerable groups, and increased the burden on educators and school staff. In Indonesia, budget reductions have most severely affected affirmative programs and rural infrastructure. In the UK, early childhood education and local public schooling have been the hardest hit. The study advocates for a socially just and equity-oriented reformulation of education budget policies.